2001
DOI: 10.1258/0022215011908487
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological considerations and clinical features of ENT tuberculosis

Abstract: Between 1 April 1996 and 30 June 1997, 1003 ear, nose and throat (ENT) outpatients and 340 inpatients diagnosed as having pulmonary tuberculosis were analysed for ENT manifestations of tuberculosis to determine the relationship to sputum positivity, whether any high risk factors exist for the ENT manifestations as compared to other pulmonary tuberculosis patients, and the response to anti-tubercular treatment. The commonest ENT manifestation was found to be laryngitis (seven cases), which was more common in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…14 The clinical features have changed over the years. 7 It used to present as the triad: pain-free otorrhea, multiple tympanic membrane perforation, and peripheral facial palsy. Its current presentation has become polymorphic.…”
Section: Review Of the Literature And The Diffe-rential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…14 The clinical features have changed over the years. 7 It used to present as the triad: pain-free otorrhea, multiple tympanic membrane perforation, and peripheral facial palsy. Its current presentation has become polymorphic.…”
Section: Review Of the Literature And The Diffe-rential Diagnosismentioning
confidence: 99%
“…3 Factors that have led to an increased incidence of tuberculosis in past decades include: the increased prevalence of HIV infection; an increased incidence of people living in poor social and economic conditions; increased resistance to anti-tuberculosis therapy; the development of resistant bacilli; drug dependency; diabetes; and alcoholism. [3][4][5][6][7][8] In the head and neck tuberculosis affects mostly the larynx, and to a lesser degree, the middle and external ear, the tonsils, neck lymph nodes, the pharynx, the mouth and salivary glands. 4,7,8 In the beginning of the 20th century, tuberculosis caused 3% to 5% of chronic suppurative otitis media cases; this rate decreased with the advent of anti-tuberculosis therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common infl ammatory lesion was tuberculosis (40%). Neeta Kulkarni et al (1996) [4] in an epidemiological and clinical study of ENT tuberculosis reported that the commonest presenting feature in all the patients was hoarseness. Similar conclusion was drawn by Essad M (2001) [5].The most common ENT manifestation of tuberculosis was tubercular laryngitis, which was more common in patients diagnosed of pulmonary tuberculosis especially defaulters of previous ATT therapy and relapse cases.…”
Section: Introductionmentioning
confidence: 99%
“…3 Commonest manifestation of otolaryngological tuberculosis excluding cervical lympahedenitis is laryngitis, but a wide spectrum of cases is encountered now-a-days. 4 Here we present a series of cases of various manifestations of tuberculosis encountered in our ENT practice, commonest manifestation being cervical lymphadenopathy. The array includes number of presentations of lupus vulgaris of face, tuberculous infection of a preauricular sinus, tuberculous osteomyelitis of mastoid bone, laryngeal tuberculosis and many more varieties.…”
Section: Introductionmentioning
confidence: 99%